VELOCITY-SHEAR-INDUCED MODE COUPLING IN THE SOLAR ATMOSPHERE AND SOLAR WIND: IMPLICATIONS FOR PLASMA HEATING AND MHD TURBULENCE - Hollweg, Joseph V.; Kaghashvili, Edisher Kh; Chandran, Benjamin D. G. (The Astrophysical journal, 2013)
We analytically consider how velocity shear in the corona and solar wind can cause an initial Alfven wave to drive up other propagating signals. The process is similar to the familiar coupling into other modes induced by non-WKB refraction in an inhomogeneous plasma, except here the refraction is a consequence of velocity shear. We limit our discussion to a low-beta plasma, and ignore couplings into signals resembling the slow mode. If the initial Alfven wave is propagating nearly parallel to the background magnetic field, then the induced signals are mainly a forward-going (i.e., propagating in the same sense as the original Alfven wave) fast mode, and a driven signal propagating like a forward-going Alfven wave but polarized like the fast mode; both signals are compressive and subject to damping by the Landau resonance. For an initial Alfven wave propagating obliquely with respect to the magnetic field, the induced signals are mainly forward- and backward-going fast modes, and a driven signal propagating like a forward-going Alfven wave but polarized like the fast mode; these signals are all compressive and subject to damping by the Landau resonance. A backward-going Alfven wave, thought to be important in the development of MHD turbulence, is also produced, but it is very weak. However, we suggest that for oblique propagation of the initial Alfven wave the induced fast-polarized signal propagating like a forward-going Alfven wave may interact coherently with the initial Alfven wave and distort it at a strong-turbulence-like rate.